Poly(trimethylene carbonate-co-caprolactone): An emerging drug delivery nanosystem in pharmaceutics - Hossain, Md. Sanower; Mohamed, Farahidah; Mohd Shafri, Mohd Affendi (Techno-Press, Ltd., 2020)
As conventional drug delivery system is being improved rapidly by target-based drug delivery system, finding suitable Drug Delivery System (DDS) for new drugs remains a challenge. Although there are many drug delivery vehicles in existence, a significant improvement is required to some DDS such as for local, implant-based treatments used for musculoskeletal infections. Many polymers have been considered for providing the improvement in DDS. Synthetic polymer, for example, has gained popularity for broad-spectrum physicochemical and mechanical properties. This article reviews the biomedical applications of poly(TriMethylene Carbonate-co-Caprolactone) (PTMCC), which has attracted attention due to its biocompatibility, biodegradability and rubber-like properties. Its synthesis, physical properties, and degradation are also discussed here. Although it is relatively new in biomedical applications, it is readily usable for the fabrication of differing format of DDS of superior mechanical strength and degradation properties. The use of PTMCC is expected to increase in coming years as more is revealed about its potentials.